(3GdOQ GdefJXe aj HjGf EgOGA GdbQH ddfHi Udi Gddg Ydjg hSdes - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JfXje SejJg GdOQ GdefJXe ai HjGf EgOGA GdbQH ddfHi Udi Gddg Ydjg hSde hgh eG CNHQfG GdYdGeI GdeMOK CHh HcQ Hf CHj YeQ GdSGHb s
(3BNQgG (B:s
(3dCf GdCaYGd GfJgi hGddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs